Unusual sensory features are related to resting-state cardiac vagus nerve activity in autism spectrum disorders. (May 2016) - Matsushima, Kanae; Matsubayashi, Jun; Toichi, Motomi; Funabiki, Yasuko; Kato, Takeo; Awaya, Tomonari; Kato, Toshihiro
Highlights: Children with ASD have lower vagus nerve activity than typical developing children. Vagus nerve activity was associated with visual/auditory sensitivity in ASD. Restricted and stereotypic behaviors also correlate with vagus nerve activity. Lower vagus nerve activity may lead to difficulty regulating behavioral responses. Abstract: The relationship between unusual sensory features (hyper-reactivity, hypo-reactivity, and unusual sensory interests) and the parasympathetic nervous system in autism spectrum disorder (ASD) has recently garnered interest. The purpose of this study was to investigate whether unusual sensory features are associated with resting-state cardiac vagus nerve activity in ASD children. Electrocardiogram signals were recorded during three 2-min resting periods to quantify the high frequency (HF) component of heart rate variability (HRV) in 37 children with ASD aged 6–12 and 32 typically developing children. Parent-reported questionnaires (Short Sensory Profile, SSP; Social Responsiveness Scale-2, SRS-2) assessed atypical sensory behaviors in daily life and autistic traits. Children with ASD consistently showed lower HF-HRV than typically developing children across the three resting periods. The SSP " Visual/Auditory Sensitivity " score was correlated with resting-state HF-HRV in the ASD group, indicating that ASD children with more severe visual/auditory hyper-reactivity in daily life have lower vagus nerve activity. The SRS-2 " Restricted Interests and Repetitive Behavior " score was also correlated with resting-state HF-HRV in the ASD group. These findings suggest that ASD children with lower vagus nerve activity may have inadequate self-regulatory capacity and difficulty regulating behavioral responses to unpredictable and unavoidable visual/auditory stimuli in daily life.